God"s household and the poor in contextual ecclesiology - Vos, Casparus Johannes Adam (HTS teologiese studies, 2001)
As a consequence of the bipolar tension between theory and practice, experience (considered in the South African context) influences the church's reflection on Practical Theology. Insight into the economic system of the Mediterranean world helps us to understand the complexities involved in positioning poverty, as well as the role of the New Testament faith community in its interaction with the poor. The social system in the ancient world, within which poverty was encountered, cautions us against taking a simplistic view of the poor. We cannot duplicate social systems and impose them on current situations. The New Testament, which is set against a particular system, speaks of the Kingdom of God as a place where the poor must be cared for. The New Testament (especially the Gospel of John) lets us understand that a church, which has a family orientation as its basis, should provide a home for the poor.